Expert Indexing in Oracle Database 11g Maximum Performance for Your Database - Kuhn, Darl.; Alapati, Sam R.; Padfield, Bill.; SpringerLink (Online service) (Berkeley, CA : Apress, 2011)
Expert Indexing in Oracle Database 11g is about the one database structure at the heart of almost all performance concerns: the index. Database system performance is one of the top concerns in information technology today. Administrators struggle to keep up with the explosion of access and activity driven by the proliferation of computing into everything from phones to tablets to PCs in our increasingly connected world. At the heart of any good-performing database lies a sound indexing strategy that makes appropriate use of indexing, and especially of the vendor-specific indexing features on offer. Few databases fully exploit the wealth of data access mechanisms provided by Oracle. Expert Indexing in Oracle Database 11g helps by bringing together information indexing and how to use it into one, convenient and blissfully short volume that you can read quickly and have at your fingertips for reference. Learn the different types of indices available and when each is best applied. Recognize when queries aren$1 (Bt using indices as you intend. Manage your indexing for maximum performance. Let Expert Indexing in Oracle Database 11g be your guide to deep mastery of the most fundamental performance optimization structure in Oracle Database. Explains how indices work, how they help, and how they hinder Demystifies the various index choices Describes the database administration chores associated with indicess
Keywords: Computer science; Database management; Computer Science; Database Management